The effect of emotional intelligence on the learning independence of students on distance learning - Desi Nori Sahputri; Rian Vebrianto (Universitas Ahmad Dahlan, 2022)
This research was conducted to see the effect of limited face-to-face learning on independent learning on the emotional intelligence of MIN 3 Pekanbaru students at the Pekanbaru Private Islamic Elementary School. The type of research is associative. The sample used was 66 students of MIN 3 Pekanbaru and was selected by purposive sampling. then the conclusion is that the significance value of the data is 0.200 > 0.05 so the data is said to be normal. Furthermore, by doing a linearity test using the ANOVA table, it is known that limited face-to-face learning affects student learning independence because the significance value is 0.000 <0.05. Furthermore, by conducting a correlation test, it is known that limited face-to-face learning has a positive effect on student learning independence. With a large influence of 24.5%.